2016
DOI: 10.1016/j.socscimed.2016.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Do minimum wages improve early life health? Evidence from developing countries

Abstract: The impact of legislated minimum wages on the early-life health of children living in low and middle-income countries has not been examined. For our analyses, we used data from the Demographic and Household Surveys (DHS) from 57 countries conducted between 1999 and 2013. Our analyses focus on height-for-age z scores (HAZ) for children under 5 years of age who were surveyed as part of the DHS. To identify the causal effect of minimum wages, we utilized plausibly exogenous variation in the legislated minimum wag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…I regard the Komro et al study as less convincing, most importantly because it fails to compare effects for more-versus less-affected groups. In contrast, I find the Wehby et al paper convincing because it shows results for less-educated but not more-educated mothers, presents robustness analyses, and reports that the effects are contemporaneous but not lagged-as we would expect in a study of birthweight Majid et al (2016). report adverse effects on height for weight of children under age 5.…”
mentioning
confidence: 68%
See 2 more Smart Citations
“…I regard the Komro et al study as less convincing, most importantly because it fails to compare effects for more-versus less-affected groups. In contrast, I find the Wehby et al paper convincing because it shows results for less-educated but not more-educated mothers, presents robustness analyses, and reports that the effects are contemporaneous but not lagged-as we would expect in a study of birthweight Majid et al (2016). report adverse effects on height for weight of children under age 5.…”
mentioning
confidence: 68%
“…Some studies discuss the potential effects of minimum wages on own health or on children's health and human capital via minimum wages raising the opportunity cost of leisure (or causing job loss) and hence affecting the allocation of time (e.g., Horn et al, 2017). 14 Time can be an input to the production of one's own health (Grossman, 1972), the production of children's human capital and health (Leibowitz, 2003), or the provision of health care to family members (Majid et al, 2016). Again, these effects may vary depending on income, or the characteristics of who is affected, making the predicted effects of higher minimum wages ambiguous.…”
Section: Minimum Wages and Health And Related Behaviorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has examined minimum wage in low- and middle-income countries in relation to child malnutrition within a household resource allocation framework. One longitudinal study found an overall harmful association with child stunting from gestational exposure to minimum wage, but underweight and overweight were grouped on a continuous Z score and there were regional differences in results, with adverse outcomes found in South Asia and improved outcomes in Latin America ( 12 ) . In another multi-country longitudinal study, countries with a 10 % or more increase in PPP-adjusted minimum wage showed a significant decline in stunting, and anthropometric failure (and a non-significant decline in underweight and wasting), compared to countries without a policy change ( 13 ) .…”
Section: Discussionmentioning
confidence: 99%
“…There have been few longitudinal or quasi-experimental studies of the relationship between minimum wage and health in low- and middle-income countries. One longitudinal multi-country study reported mixed associations of minimum wage with early-life health outcomes measured by height-for-age Z -scores ( 12 ) , while another showed protective effects against child stunting and a composite measure of anthropometric failure ( 13 ) . In a cross-sectional multi-country study of adult non-pregnant women, the relationship between minimum wage and excess weight varied by country income level ( 14 ) .…”
mentioning
confidence: 99%